Gamification in Physical Education Learning: A Strategy to Increase Student Participation at Universitas Terbuka - Mudayat, Mudayat (Performa, 2025)
This study seeks to evaluate how gamification affects student motivation, engagement, and learning in an online Physical Education course at Universitas Terbuka. A sample of 40 out of 240 students enrolled in the 4th semester of the program was drawn using purposive sampling. The participants responded to a 12-item acknowledgment scale measuring four aspects of gamification: motivational aspects of games, participation and engagement, skills, and overall learning experiences. Based on the analysis of the data collected, findings point out that gamification positively affects student motivation and participation. A significant number of students (92.5%) agreed that new activities based on games made learning processes more enjoyable, and 90% of students said that gamification lessened the boredom encountered in online learning. Although underperforming students were able to increase their understanding of theoretical concepts taught in class, there was a lack of improvement in the performance of some students who were active in independent physical skill practice with only 75% agreeing that the tasks fostered the development of independent physical skills. Most of the students supported the continuation of gamification in the Physical Education course and 95% wanted the inclusion of more game-oriented learning in future lessons. The results indicate that although gamification increases motivation and participation, other strategies are needed to develop practical skills in the context of online Physical Education classes.